Evolution of ion acoustic solitary waves in pulsar wind - Singh, Kuldeep; Kakad, Amar; Kakad, Bharati; Saini, Nareshpal Singh (My University, 2021)
We have studied the evolution of ion acoustic solitary waves (IASWs) in pulsar wind. The pulsar wind is modelled by considering a weakly relativistic unmagnetized collisionless plasma comprised of relativistic ions and superthermal electrons and positrons. Through fluid simulations, we have demonstrated that the localized ion density perturbations generated in the polar wind plasma can evolve the relativistic IASW pulses. It is found that the concentration of positrons, relativistic factor, superthermality of electrons, and positrons have a significant influence on the dynamical evolution of IASW pulses. Our results may provide insight to understand the evolution of IASW pulses and their role in astrophysical plasmas, especially in the relativistic pulsar winds with supernova outflow, which is responsible for the production of superthermal particles and relativistic ions.
Keywords: Plasmas; Waves